Civil society and democratization: The role of service‐providing organizations amid closing civic spaces. (17th January 2023) - Moldavanova, Alisa; Onishi, Tamaki; Toepler, Stefan
Abstract: This article argues that current democracy promotion strategies relying on rights‐claiming advocacy NGOs are falling short of their democratization goals, as authoritarian regimes are closing the space through restrictions on the NGOs that attempt to carry them out. In response, we suggest a reexamination of earlier approaches to involving civil society in democratization efforts by shifting the focus back on service‐providing civil society organizations that have largely become side‐lined in democracy‐building agendas. Specifically, service providers tend to be more capable of functioning "under the radar" thus contributing to democracy in both direct and indirect ways, and thus escaping closing space restrictions. The key concerns about their independence from the state, as well as under what conditions the state may be less successful in coopting the independent service‐providers, however, remain unresolved and warrant future research.